2008
DOI: 10.5271/sjweh.1243
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental tobacco smoke and health effects among hospitality workers in Sweden—before and after the implementation of a smoke-free law

Abstract: Refers to the following text of the Journal: 2005;31(1):0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 43 publications
8
46
0
2
Order By: Relevance
“…It is clear that following workplace smoke-free laws, there are remarkably consistent results (Allwright et al 2005;Eagan et al 2006;Goodman et al 2007;Larsson et al 2008;Menzies et al 2006;Valente et al 2007) on selfreported improvements in respiratory and irritant symptoms. Studies consistently find reductions in symptoms of between 20 and 50%.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is clear that following workplace smoke-free laws, there are remarkably consistent results (Allwright et al 2005;Eagan et al 2006;Goodman et al 2007;Larsson et al 2008;Menzies et al 2006;Valente et al 2007) on selfreported improvements in respiratory and irritant symptoms. Studies consistently find reductions in symptoms of between 20 and 50%.…”
Section: Discussionmentioning
confidence: 91%
“…In Norway, a 19% drop in respiratory symptoms was observed 5 months post the ban, among workers in the hospitality industry (Eagan et al 2006). An even greater decline of 50% in respiratory and sensory symptoms was reported after a 12-month follow-up, post the Swedish ban among nonsmoking gaming workers (Larsson et al 2008). In Spain, which does not have a comprehensive smoke-free laws in place, reported a maximum decline of 72% in self-reported respiratory symptoms 12 months post the ban in a followup study among hospitality workers (Fernández et al 2009).…”
Section: Questionnaire Based Respiratory Health Outcomesmentioning
confidence: 98%
“…Studies from developed countries such as Finland (Heloma & Jaakkola, 2003), The Netherlands (Wilson, Edwards, Maher, Nathe, & Jalali, 2007), Scotland (Haw & Gruer, 2007), and Spain (Nebot et al, 2009) have shown a considerable reduction in workplace and restaurant SHS exposure and in respiratory symptoms among hospitality workers (Larsson, Boethius, Axelsson, & Montgomery, 2008) after implementation of a smoke-free ordinance. However, evidence from Asian countries remains limited.…”
Section: Effect Of Media Campaigns and Smoke-freementioning
confidence: 98%
“…Multiple studies have documented the positive short-term impact of smoke-free legislation in the improvement of self-reported sensory and respiratory symptoms as well as of lung function measures (Allwright et al, 2005;Ayres et al, 2009;Eagan, Hetland, & Aaro, 2006;Eisner, Smith, & Blanc, 1998;Farrelly et al, 2005;Lai et al, 2011;Larsson, Boethius, Axelsson, & Montgomery, 2008;Menzies et al, 2006;Pearson, Windsor, El-Mohandes, & Perry, 2009;Schoj et al, 2010;Skogstad et al, 2006;Wakefield, Cameron, Inglis, Letcher, & Durkin, 2005). On the contrary, incomplete bans do not improve workers' respiratory health (Fernandez et al, 2009).…”
Section: Respiratory and Sensory Symptomsmentioning
confidence: 99%